Plasmon-driven methanol oxidation on PtAg nanoalloys prepared by improved pulsed laser deposition. (30th September 2022) - Wang, Junpeng; Guo, Longfei; Pan, Bowei; Jin, Tao; Li, Zhen; Tang, Quan; Andreazza, Pascal; Chen, Yu; An, Liang; Chen, Fuyi
Abstract : We proposed a general strategy for alloying silver and platinum elements into single-phase solid-solution nanoparticles with arbitrarily desired composition by bonding pure Pt targets with pure Ag strips in an improved pulsed laser deposition. Abstract : The methanol oxidation reaction (MOR) is crucial in many energy-conversion devices. Although intensive efforts have been devoted to improving the MOR catalytic activity of Pt-based catalysts by treatment or alloying, enhancing the MOR catalyst performance utilizing solar energy has been less investigated. PtAg nanoalloys, combining the intrinsic catalytic activity of Pt toward the MOR with the visible spectrum plasmonic response of Ag, are expected to be a good MOR catalyst for solar energy, however, it remains challenging to incorporate these immiscible elements into a nanoalloy in a controlled way using conventional synthetic techniques. Herein, we proposed a general strategy for alloying silver and platinum elements into single-phase solid-solution nanoparticles with arbitrarily desired composition by bonding pure Pt targets with pure Ag strips in an improved pulsed laser deposition. The as-prepared PtAg nanoalloys show two crystalline phases and an average particle size of about 4 nm. To prove utility, we use the PtAg nanoalloys as support-free MOR catalysts anchored on the surface of a glassy carbon electrode solidly and uniformly. The PtAg nanoalloys exhibit a mass catalytic activity of 3.6 A mg −1, which is 4.5 times higher than that of the commercial Pt/C catalyst. Besides, the PtAg nanoalloys exhibit a promising regenerability after reactivation by cyclic voltammetry. Furthermore, the MOR catalytic activity of PtAg nanoalloys increased by 16% under irradiation by simulated sunlight, which is attributed to the surface plasmon resonance as ascertained from the UV-vis absorption spectra and photocurrent response experiments. These studies are believed to provide a new strategy for the enhancement of MOR catalytic activity with visible light as the driving force.